Peran Kepala Sekolah Sebagai Manajer dalam Implementasi Kurikulum Merdeka - Sudjiati, Sudjiati; Muhdi, Muhdi (PGRI Kota Semarang, 2024)
This research uses a qualitative method with a phenomenological approach. The research was carried out at SD Negeri Srondol Kulon 02, Banyumanik District, Semarang City starting in June 2023. Data collection techniques in this research used interviews, observation and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. Research results (1) The role of the school principal as a manager in planning the independent curriculum includes a) setting goals for implementing the independent curriculum; b) preparing an independent curriculum program; c) prepare a budget for implementing the independent curriculum; d) organize a team of implementing coordinators. (2). The role of the school principal as a manager in organizing the independent curriculum is 1) allocating resources; 2) formulate and assign tasks; 3) establish necessary procedures; 4) establish an organizational structure that shows the lines of authority and responsibility. (3) The role of the school principal as a manager in implementing the independent curriculum, such as a) consultative and asymmetric mentoring activities; b) provide strengthening of school human resources; c) learning activities through a new paradigm; d) data-based planning; e) digitalization of schools (4) The role of the principal as a manager in supervising the independent curriculum includes internal supervision carried out by the school principal and supervisor, then external supervision carried out by the school committee, seen from a technical perspective, supervision is carried out with two approaches, namely technical direct supervision and indirect supervision in report form. Apart from that, supervision of 1) assessment standards; 2) assessment; 3) the results of the assessment are in the form of a project report; 4) follow-up of project activities. The conclusion is that the role of the school principal as a manager in implementing the independent curriculum goes through the stages of planning, organizing, implementing and monitoring, all carried out continuously and together with school stakeholders. Suggestions that in the future school principals should embrace all parties more in policy making